CONTROL PROBLEMS FOR NONLINEAR VARIATIONAL EVOLUTION INEQUALITIES - Su Jin Cheon (Tạp chí Khoa học Đại học Đà Lạt)
In this paper, we deal with the approximate control-ability for the nonlinear functional differential equation governed by the variational inequality in Hilbert spaces and present a general theorems under which previous results easily follow. The common research direction is to find conditions on the nonlinear term such that control-ability is preserved under perturbation.